Adapting the World Health Organization iSupport Dementia program to the Indonesian socio-cultural context - Turana, Yuda; Kristian, Kevin; Suswanti, Ika; Sani, Tara Puspitarini; Handajani, Yvonne Suzy; Tran, Kham; Nguyen, Tuan Anh (Frontiers in Public Health, 2023)
Background Providing care for people with dementia (PwD) without sufficient understanding of the condition might negatively affect the wellbeing of the caregivers, given the lengthy care and progressive nature of the disease. The iSupport for dementia developed by World Health Organization (WHO) is a self-administered training manual for caregivers of PwD, adaptable to local cultures and contexts. This manual needs translation and adaptation to produce a culturally appropriate version for use in Indonesia. This study reports the outcomes and lessons learnt from our translation and adaptation of iSupport content into Bahasa Indonesia. Methods The original iSupport content was translated and adapted using the WHO iSupport Adaptation and Implementation Guidelines. The process included forward translation, expert panel review, backward translation, and harmonization. The adaptation process included Focus Group Discussions (FGD), involving family caregivers, professional care workers, professional psychological health experts, and Alzheimer's Indonesia representatives. The respondents were asked to express their opinions about the WHO iSupport program, which comprises five modules and 23 lessons covering well-established topics on dementia. They were also asked to suggest improvements and their personal experiences compared to the adaptations applied in the iSupport. Results Two experts, 10 professional care workers, and eight family caregivers participated in the FGD. Overall, all participants had positive views of the iSupport material. The expert panel identified the need to reformulate definitions, recommendations, and local case studies to fine-tune the original contents to local knowledge and practices. Based on the feedback in the qualitative appraisal, several improvements regarding the language and diction, additional relevant and concrete examples, personal names and cultural habits, and customs and traditions were addressed. Conclusions The translation and adaptation of the iSupport into the Indonesian context have shown some changes needed to make the iSupport content culturally and linguistically appropriate for Indonesian end users. In addition, given the broad spectrum of dementia, various case illustrations have been added to improve the understanding of care in particular situations. Future studies are needed to evaluate the efficacy of the adapted iSupport in improving the quality of life of PwD and their caregivers.